ANALISIS RESPON DAYA PEMANAS PADA FASILITAS HEATING CONTROL - Prasetya Hariyanto, Kevin; Zuliantoni; Witanto, Yovan; Valentina, Pricylia (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2025)
Currently the Fassip-01 strand to Fassip-07 uses a control system of two positions (on-off) in controlling heaters to maintain stopping conditions when experiments are carried out. Nuclear Termofluidal System Research Group Develops the Heating Control Facility that functions as a Heating Control System Test Facility using PID system control (proportional integral derivative) to overcome the problem of existing residual heat due to the use of the Kend system This test was conducted to find out the analysis of 4 heater power before the experiment took place and analyzed RTM (Risetime) Setpoint 40.45, and 50 degrees. In this experiment the method used was an experiment so that the results were obtained in the form of accuracy values, heater positions, high energy consumption, poor power settings, large residual heat and time difference ratio in each setpoint.